A perda de arroz e o nexus água-energia-alimento: estratégias das agroindústrias arrozeiras do Rio Grande do Sul - Oliveira, Gabriel Mutschal de (2022)
The present study aimed to broadly identify the loss of rice and economic and environmental implications and how the actors in the rice supply chain are acting in relation to the promotion of security: food and energy. So, which characterized the production and loss of rice in Brazil, South Region and Rio Grande do Sul, considering the area of planting, production, yield and loss, analyzing the strategic postures of the analyzed companies facing the problem of rice loss in Brazil and its implications. Thus, it was divided into two stages: the first with a quantitative approach to assess through secondary data sourced from the FAOSTAT portal (FAO, 2019) and from the National Supply Company of CONAB, the loss and energy potential of the grain being divided in categories of analysis of organizational strategies, alignment with the Nexus and actors in the supply chain. The results suggest, to conclude that Rio Grande do Sul, presents itself as the main producer in Brazil, corroborating with the literature found. Still, in this sense of productivity, at the national level, the Rice Sector shows retraction. However, the high yield of Rio Grande do Sul complements any loss or drop in productivity, maintaining food security in relation to rice in the country. It is possible to infer that there was an oscillation in the planted area in relation to the total in Brazil. The average for the South region and RS stands out, 1,076,118.91 hectares, which corresponds to approximately 50% of the national average. These results call attention to the convergence of eco-sustainable discourses, and the need to expand more hectares or encourage deforestation for rural purposes. We emphasize the view that organizations that have solid values and ethical business conduct tend to prosper. Generating a bias to the Nexus. Suggesting future research related to gauging the formula adapted in this study to analyze the loss of rice and implications of the Nexus in the strategy of consolidated organizations.